Metaphors of chaos and metonymies In the front-page headlines of the tabloid Trome - Solís Aroni, Nora (2021)
Discourse has a communicative purpose. In the journalistic genre of tabloids, the news tries to impact the reader with striking headlines on any topic of interest; this can be seen in the headlines of one of the top-selling newspapers in Peru: Trome, a tabloid that stands out for its striking headlines, due to the use of phraseology with a metaphorical sense. This research describes conceptual metaphors in the headlines of Trome and focuses on the description of a prototypical form: chaos and one of its effects: punishment. The data collected correspond to the years 2010, 2013, 2016, 2017, 2018 and 2019, and were taken from its digital version.